Lithium metal three-dimensional porous material, secondary battery and electric device

By using lithium metal three-dimensional porous materials in lithium metal batteries and using the combined structure of the matrix layer and polymer layer, the shortcomings in the ratio performance and cycle life of lithium metal batteries are solved, and higher cycle stability and energy density are achieved.

CN119725463AActive Publication Date: 2025-03-28ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411923397.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

In actual applications, existing lithium metal batteries face problems such as poor rate performance, limited cycle life and low safety. Especially due to the three-dimensional material design with high specific surface area, the side reaction between lithium ions and the electrolyte is severe when embedded and disengaged, resulting in a shortening of the battery cycle life.

Method used

A lithium metal three-dimensional porous material is used, which consists of a matrix layer and a polymer layer. The substrate layer includes a three-dimensional conductive metal and a lithium metal filled inside its pores. The polymer layer has excellent ionic and electron conductivity, at least partially coated on the outer periphery of the substrate layer, forming a three-dimensional porous structure.

Benefits of technology

By improving the embedding and removal efficiency of lithium ions, reducing the side reaction between lithium metal and electrolyte, significantly improving the cycle stability and energy density of secondary batteries, enhancing mechanical stability and extending the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005208612470000141
    Figure BDA0005208612470000141
  • Figure BDA0005208612470000151
    Figure BDA0005208612470000151
  • Figure BDA0005208612470000161
    Figure BDA0005208612470000161
Patent Text Reader

Abstract

The invention discloses a lithium metal three-dimensional porous material, a secondary battery and an electric device, and belongs to the technical field of secondary batteries, the lithium metal three-dimensional porous material comprises a matrix layer and a polymer layer at least partially coating the periphery of the matrix layer, the matrix layer comprises three-dimensional conductive metal and lithium metal filled in the three-dimensional conductive metal. The lithium metal three-dimensional porous material disclosed by the invention has the characteristics of high specific surface area and high interface stability, the energy density of a secondary battery can be effectively improved, the polymer layer coated on the periphery has excellent mechanical stability, the solubility to lithium salt is good, the interface stability can be effectively improved, and the lithium metal three-dimensional porous material has a good application prospect. The polymer layer can isolate direct contact between lithium metal and electrolyte, side reaction of contact between the lithium metal and the electrolyte is reduced, the matrix layer provides high-activity deposition sites and sufficient deposition space for lithium ions in the charging process, and the rate performance and the cycle performance of the secondary battery are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a lithium metal three-dimensional porous material, a secondary battery and an electrical device. Background Art

[0002] With the rapid development of science and technology and the widespread popularity of electronic devices, electric vehicles and other fields, people's demand for high-efficiency and high-energy-density batteries is growing. Traditional battery technology can no longer meet this growing demand, so it is necessary to develop new battery technology to meet the urgent needs of the market.

[0003] Among these new batteries, lithium metal batteries have attracted much attention because the lithium metal battery system has a higher energy density. The gram capacity of lithium metal is as high as 3860mAh / g (11 times higher than graphite), and the redox potential is as low as -3.04V compared with the standard hydrogen electrode (which means the discharge voltage platform is higher). According to our calculations, if the graphite negative electrode in the battery is replaced with lithium metal, the volume ED gain of the battery will increase by up to 62%, and the weight ED gain can increase by up to 45%, which means that at the same volume and weight, the battery can store more energy, and electric vehicles, mobile phones and other devices will have a longer battery life.

[0004] However, lithium metal batteries face many challenges in practical applications, such as impractical rate performance, unsafe cycling conditions and limited cycle life. In order to solve these problems, researchers have done a lot of work, including surface modification of lithium metal and construction of three-dimensional / composite materials. However, conventional three-dimensional material design also has many defects. For example, although the high specific surface area is conducive to the rapid insertion and extraction of lithium ions, it also exacerbates the side reactions between lithium metal and electrolyte. Lithium metal and electrolyte are quickly consumed during the charge and discharge cycle, and the battery cycle life is greatly shortened.

[0005] In view of this, this application is filed. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a lithium metal three-dimensional porous material, a secondary battery and an electrical device, which can effectively improve the cycle stability of the secondary battery.

[0007] To achieve the above-mentioned object, the first aspect of the present application provides a lithium metal three-dimensional porous material, comprising a substrate layer and a polymer layer at least partially coated on the periphery of the substrate layer, wherein the substrate layer comprises a three-dimensional conductive metal and lithium metal filled in the pores of the three-dimensional conductive metal;

[0008] The ionic conductivity of the polymer layer is 10 -5 ~1S / cm, electronic conductivity is 10 -9~10 -5 S / cm.

[0009] As an embodiment of the present application, the ionic conductivity of the polymer layer is 5.4*10 -5 ~8.9*10 -4 S / cm, the electronic conductivity is 7.4*10 -7 ~2.1*10 -5 S / cm.

[0010] As an embodiment of the present application, the three-dimensional conductive metal includes at least one of foamed copper, foamed nickel, and foamed aluminum.

[0011] As an embodiment of the present application, the porosity of the base layer is A, 10%≤A≤30%.

[0012] As an embodiment of the present application, the average pore size of the three-dimensional conductive metal is 20 to 80 μm.

[0013] As an implementation scheme of the present application, the mass percentage of the lithium metal in the matrix layer is B, which satisfies: 0.2%≤B≤1%.

[0014] As an implementation scheme of the present application, the following is satisfied: 10≤A / B≤125.

[0015] As an embodiment of the present application, the thickness of the three-dimensional conductive metal is 2 to 350 μm.

[0016] As an embodiment of the present application, the thickness of the polymer layer is 5 to 50 nm.

[0017] As an embodiment of the present application, the viscosity average molecular weight of the polymer in the polymer layer is 100,000 to 10,000,000.

[0018] The second aspect of the present application provides a method for preparing a lithium metal three-dimensional porous material, comprising the following steps:

[0019] Rolling and heat treating the three-dimensional conductive metal to obtain a pretreated three-dimensional conductive metal;

[0020] placing the pretreated three-dimensional conductive metal in a reaction solution, reacting to obtain a precursor;

[0021] Placing the precursor in an electrolyte for electrochemical deposition to obtain a lithium metal three-dimensional porous material;

[0022] The reaction solution includes a first lithium salt and a compound containing at least one of a halogen group, a sulfonate group, a sulfate group, and an epoxy group;

[0023] The electrolyte includes a second lithium salt and an organic solvent.

[0024] As an embodiment of the present application, the temperature of the heat treatment is 200 to 300° C., and the time of the heat treatment is 0.5 to 6 hours.

[0025] As an embodiment of the present application, the heat treatment is performed in a mixed atmosphere of argon and hydrogen, and the volume ratio of hydrogen to argon is (0.5-2):(18-19.5).

[0026] As an embodiment of the present application, the reaction temperature is 50 to 100° C., and the reaction time is 10 to 600 min.

[0027] As an embodiment of the present application, the concentration of the first lithium salt in the reaction solution is 0.05 to 0.8 mmol / L.

[0028] As an embodiment of the present application, the concentration of the second lithium salt in the electrolyte is 0.5 to 2 mol / L.

[0029] As an embodiment of the present application, the first lithium salt and the second lithium salt independently include at least one of LiTFSI, LiFSI, LiPF6, and LiBF4.

[0030] As an embodiment of the present application, the molecular formula of the compound containing epoxy group is C3H5O2-(C2H4O) n -C3H5O, the number average molecular weight of the compound containing epoxy group is 300-800.

[0031] A third aspect of the present application provides a secondary battery, comprising a negative electrode, wherein the negative electrode comprises the above-mentioned lithium metal three-dimensional porous material.

[0032] A fourth aspect of the present application provides an electrical device, comprising the secondary battery described above.

[0033] The beneficial effects of the present invention are as follows: the substrate layer of the lithium metal three-dimensional porous material described in the present application is a three-dimensional conductive metal with internal pores filled with metallic lithium, the polymer layer is at least partially coated on the periphery of the substrate layer, and the overall three-dimensional porous structure is presented; the lithium metal three-dimensional porous material has the characteristics of high specific surface area and high interface stability, which is conducive to the embedding and extraction of lithium ions, and can effectively improve the energy density of secondary batteries; the polymer layer coated on the periphery has excellent mechanical stability, and can be well applied to the preparation of secondary batteries, especially suitable for the preparation of lithium metal batteries, has good solubility in lithium salts, and can effectively increase interface stability; the polymer layer can isolate the direct contact between lithium metal and electrolyte, and reduce the side reactions of the contact between the two; the substrate layer provides highly active deposition sites and sufficient deposition space for lithium ions during the charging process, slowly releases the compressive stress during the charging and discharging process and the rolling process, and effectively improves the rate performance and cycle performance of the secondary battery. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0035] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0036] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0037] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0038] Unless otherwise specified, the components, raw materials or instruments used in the embodiments and comparative examples of the present invention are all commercially available raw materials or instruments, and the components and raw materials used in each parallel experiment are all of the same kind.

[0039] The embodiment of the present application provides a lithium metal three-dimensional porous material, comprising a substrate layer and a polymer layer at least partially coated on the periphery of the substrate layer, wherein the substrate layer comprises a three-dimensional conductive metal and lithium metal filled in the pores of the three-dimensional conductive metal;

[0040] The ionic conductivity of the polymer layer is 10 -5 ~1S / cm, electronic conductivity is 10 -9 ~10 -5 The substrate layer of the lithium metal three-dimensional porous material described in the present application is a three-dimensional conductive metal filled with metallic lithium, and the polymer layer is at least partially coated on the periphery of the substrate layer, presenting a three-dimensional porous structure as a whole. The ionic conductivity of the polymer layer is 10 -5 ~1S / cm, electronic conductivity is 10 -3 ~10 -2 S / cm, the lithium metal three-dimensional porous material has the characteristics of high specific surface area and high interface stability, which is conducive to the embedding and extraction of lithium ions, and can effectively improve the energy density of secondary batteries. The peripheral coated polymer layer has excellent mechanical stability and can be well applied to the preparation of secondary batteries, especially suitable for the preparation of lithium metal batteries. It has good solubility for lithium salts and can effectively increase the interface stability. The polymer layer can isolate the direct contact between lithium metal and electrolyte, and reduce the side reactions of the contact between the two. The substrate layer provides highly active deposition sites and sufficient deposition space for lithium ions during the charging process, slowly releases the compressive stress during the charging and discharging process and the rolling process, and effectively improves the cycle performance of the secondary battery.

[0041] Wherein, the ionic conductivity of the polymer layer is tested by EIS impedance test.

[0042] Specifically, the test method for the ionic conductivity of the polymer layer is: take an appropriate amount of oligomer reaction solution (a reaction solution containing a first lithium salt and a compound containing at least one of a halogen group, a sulfonate group, a sulfate group, and an epoxy group) on a thin plate, use the same method to initiate thermal polymerization, remove the thin plate to obtain a polymer film, the thickness and area of ​​the polymer film are recorded as L and S, assemble stainless steel to stainless steel symmetrically, use the polymer film as a diaphragm in the middle, perform EIS analysis, and obtain R0. The calculation formula of the ionic conductivity is as follows: L / (RoS).

[0043] Wherein, the electronic conductivity of the polymer layer is tested by a four-probe test method.

[0044] Specifically, the test method for the electronic conductivity of the polymer layer is: take an appropriate amount of oligomer reaction liquid on a thin plate, use the same method to initiate thermal polymerization, and obtain a polymer film after removing the thin plate; during the test, four equally spaced probes are pressed on the surface of the film, two of which are used to inject current, and the other two probes measure voltage. The material resistance is calculated by Ohm's law, and then the electronic conductivity is converted.

[0045] In one embodiment, the polymer layer includes at least one of PEO (polyethylene oxide), PAN (polyacrylonitrile), PVDF (polyvinylidene fluoride), PMMA (polymethyl methacrylate), and PC (polycarbonate).

[0046] The present invention uses at least one of PEO, PAN, PVDF, PMMA and PC as the polymer layer, and the polymer layer has the characteristics of good compatibility with lithium metal, high mechanical stability and the like.

[0047] In one embodiment, the ionic conductivity of the polymer layer is 5.4*10 -5 ~8.9*10 -4 S / cm, the electronic conductivity is 7.4*10 -7 ~2.1*10 -5 S / cm.

[0048] In one embodiment, the polymer layer comprises PEO, and the infrared spectrum of the polymer layer is 1080-1160 cm -1 Has characteristic peaks.

[0049] As an implementation scheme of the present application, the three-dimensional conductive metal includes at least one of foam copper, foam nickel, and foam aluminum. The present invention uses three-dimensional conductive metals such as foam copper, foam nickel, and foam aluminum as skeleton materials, which can effectively improve the structural stability of lithium metal three-dimensional porous materials. Compared with carbon materials, this type of three-dimensional conductive metal has a lower nucleation overpotential of lithium metal on its surface (nucleation overpotential refers to the energy barrier that needs to be overcome when lithium nucleates and deposits). This type of three-dimensional conductive metal is ductile and still maintains the continuity of its own conductive network during large volume expansion. At the same time, it can effectively inhibit dendrite growth and side reactions with the electrolyte to a certain extent, thereby further improving the cycle performance of the secondary battery.

[0050] In one embodiment, the porosity of the base layer is A, 10%≤A≤30%, for example, it can be 10%, 12%, 14%, 15%, 16%, 18%, 20%, 22%, 24%, 25%, 30% or a range consisting of any two of these values.

[0051] In one embodiment, the average pore size of the three-dimensional conductive metal is 20-80 μm, for example, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm or a range consisting of any two values ​​therein.

[0052] It should be noted that the porosity and average pore size of the present application are obtained by testing using conventional testing methods in the art, for example, a gas adsorption method can be used for testing.

[0053] Exemplarily, the porosity and average pore size testing method of the present application is: placing the sample in an adsorption device, passing nitrogen, measuring the change in gas volume before and after adsorption, obtaining a nitrogen adsorption-desorption curve, and converting it into porosity and average pore size through calculation.

[0054] In one embodiment, the mass percentage of the lithium metal in the matrix layer is B, which satisfies: 0.2%≤B≤1%, for example, it can be 0.2%, 0.4%, 0.5%, 0.6%, 0.8%, 1% or a range consisting of any two values ​​therein; when the mass percentage of the lithium metal in the matrix layer is within this range, the lithium metal three-dimensional porous material can be guaranteed to have a certain porosity, promote the insertion and extraction of lithium ions, and at the same time, provide highly active deposition sites and more sufficient deposition space for lithium ions during charging, offsetting the consumption of lithium elements by side reactions or dead lithium generation during the cycle. It should be noted that the mass percentage of the lithium metal in the matrix layer of the present application can be obtained by removing the lithium layer with an ethanol aqueous solution or other mildly reactive solution, and the weight loss before and after is calculated by weighing to obtain the mass percentage of the lithium metal in the matrix layer.

[0055] In one embodiment, it satisfies: 10≤A / B≤125, for example, it can be 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 125 or a range consisting of any two of these values. By controlling A / B within this range, the characteristics of high specific surface area and high interface stability can be better taken into account. The lithium metal three-dimensional porous material has better structural stability and can provide more reaction sites, thereby improving the charge storage capacity of the secondary battery, reducing the impedance of the current conduction path, ensuring that the battery can maintain a stable current output during high-power discharge, maintaining structural stability during the charge and discharge process, and effectively alleviating volume expansion and contraction during the battery charge and discharge process, avoiding breakage and shedding, which is beneficial to the insertion and extraction of lithium ions, and further improving the cycle performance of the secondary battery.

[0056] In one embodiment, the thickness of the three-dimensional conductive metal is 2 to 350 μm, for example, it can be 2 μm, 3 μm, 5 μm, 10 μm, 20 μm, 30 μm, 50 μm, 60 μm, 80 μm, 100 μm, 120 μm, 150 μm, 180 μm, 200 μm, 220 μm, 250 μm, 260 μm, 280 μm, 300 μm, 320 μm, 350 μm or a range consisting of any two of the values.

[0057] In one embodiment, the three-dimensional conductive metal has a thickness of 50-100 μm.

[0058] In one embodiment, the thickness of the polymer layer is 0.5 to 20 μm, for example, it can be 0.5 μm, 1 μm, 2 μm, 5 μm, 10 μm, 12 nm, 15 nm, 20 nm, 25 nm or a range consisting of any two of these values. By controlling the thickness of the polymer layer within this range, it is beneficial to the rapid conduction of ions, and the chain segments are not easily displaced during large volume expansion, thereby ensuring that the polymer protection does not fail after a long cycle, further improving the cycle performance.

[0059] In one embodiment, the viscosity average molecular weight of the polymer in the polymer layer is 100,000 to 10,000,000.

[0060] In one embodiment, the viscosity-average molecular weight of the polymer in the polymer layer is 300,000 to 5,000,000. By controlling the viscosity-average molecular weight of the polymer within this range, it has better structural stability, effectively alleviates volume expansion and contraction during battery charging and discharging, can fully isolate the lithium battery and the electrolyte, and the chain segments are not easily displaced during large volume expansion, thereby further improving the cycle performance.

[0061] An embodiment of the present application provides a method for preparing a lithium metal three-dimensional porous material, comprising the following steps:

[0062] Rolling and heat treating the three-dimensional conductive metal to obtain a pretreated three-dimensional conductive metal;

[0063] placing the pretreated three-dimensional conductive metal in a reaction solution, reacting to obtain a precursor;

[0064] Placing the precursor in an electrolyte for electrochemical deposition to obtain a lithium metal three-dimensional porous material;

[0065] The reaction solution includes a first lithium salt and a compound containing at least one of a halogen group, a sulfonate group, a sulfate group, and an epoxy group;

[0066] The electrolyte includes a second lithium salt and an organic solvent.

[0067] The present application prepares a lithium metal three-dimensional porous material through the above-mentioned preparation method. The base layer of the lithium metal three-dimensional porous material is a three-dimensional conductive metal filled with metallic lithium inside, and the PEO (polyethylene oxide) layer is coated on the periphery of the base layer. The pore diameter of the base layer is 20 to 80 μm, and the porosity is 10 to 25%, presenting a three-dimensional porous structure as a whole.

[0068] Among them, rolling the three-dimensional conductive metal can compress the internal porous space to reach a preset thickness, and then heat treating it to effectively reduce the oxide on the surface of the three-dimensional conductive metal into a three-dimensional conductive metal, and then placing it in a reaction solution for in-situ reaction to generate the PEO film, and finally electrolyzing it, lithium ions pass through the PEO film (the PEO layer has a high ionic conductivity and low electronic conductivity, so during the deposition process, lithium ions will pass through the PEO layer to reach the inside of the three-dimensional conductive metal), reacting an electronic reduction reaction, thereby forming lithium metal inside the three-dimensional conductive metal.

[0069] Among them, the present invention uses in-situ polymerization with a compound containing at least one of a halogen group, a sulfonate group, a sulfate group, and an epoxy group to obtain the above-mentioned polymer layer with ionic conductivity and electronic conductivity. The generated polymer has a high amorphous ratio (0-10%), which is beneficial to the rapid conduction of ions. At the same time, after in-situ polymerization, the chain segments are not easily displaced during the large volume expansion process, thereby ensuring that the polymer protection is not invalid after a long cycle.

[0070] In one embodiment, before rolling, the thickness of the three-dimensional conductive metal is 10 to 500 μm, for example, it can be 10 μm, 20 μm, 30 μm, 50 μm, 60 μm, 80 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm, 500 μm or a range consisting of any two of these values.

[0071] In one embodiment, before rolling, the porosity of the three-dimensional conductive metal is 50-99%, for example, it can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 99% or a range consisting of any two of these values.

[0072] In one embodiment, before rolling, the average pore size of the three-dimensional conductive metal is 20 to 80 μm, for example, 20 to 80 μm, for example, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm or a range consisting of any two of these values.

[0073] In one embodiment, the roller pressing pressure is 1 to 100 MPa, for example, 1 MPa, 2 MPa, 5 MPa, 10 MPa, 20 MPa, 30 MPa, 40 MPa, 50 MPa, 60 MPa, 70 MPa, 80 MPa, 90 MPa, 100 MPa or a range consisting of any two of these values.

[0074] In one embodiment, the heat treatment temperature is 200-300°C, for example, it can be 200°C, 220°C, 240°C, 250°C, 260°C, 280°C, 300°C or a range consisting of any two of these values.

[0075] In one embodiment, the heat treatment time is 0.5 to 6 h, for example, it can be 0.5 h, 0.6 h, 0.8 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, 6 h or a range consisting of any two values ​​therein.

[0076] In one embodiment, the heat treatment is carried out in a mixed atmosphere of argon and hydrogen, and the volume ratio of hydrogen to argon is (0.5-2):(18-19.5), for example, it can be 0.5:19.5, 0.8:19.2, 1:19, 1.2:18.8, 1.5:18.5, 1.8:18.2, 2:18 or a range consisting of any two of these values.

[0077] In one embodiment, the reaction temperature is 50-100°C, for example, it can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C or a range consisting of any two of the values.

[0078] In one embodiment, the reaction time is 10 to 600 min, for example, it can be 10 min, 20 min, 40 min, 50 min, 60 min, 100 min, 200 min, 300 min, 400 min, 500 min, 600 min or a range consisting of any two values ​​therein.

[0079] In one embodiment, the concentration of the first lithium salt in the reaction solution is 0.05 to 0.8 mmol / L, for example, 0.05 mmol / L, 0.08 mmol / L, 0.1 mmol / L, 0.2 mmol / L, 0.3 mmol / L, 0.4 mmol / L, 0.5 mmol / L, 0.6 mmol / L, 0.7 mmol / L, 0.8 mmol / L or a range consisting of any two of these values.

[0080] In one embodiment, the concentration of the second lithium salt in the electrolyte is 0.5-2 mol / L, for example, 0.5 mol / L, 0.6 mol / L, 0.8 mol / L, 1 mol / L, 1.2 mol / L, 1.5 mol / L, 1.8 mol / L, or 2 mol / L.

[0081] In one embodiment, the first lithium salt and the second lithium salt independently include at least one of LiTFSI (lithium bis(trifluoromethylsulfonyl)imide), LiFSI (lithium bis(fluorosulfonyl)imide), LiPF6 (lithium hexafluorophosphate), and LiBF4 (lithium tetrafluoroborate).

[0082] In one embodiment, the molecular formula of the epoxy group-containing compound is C3H5O2-(C2H4O) n -C3H5O, the number average molecular weight of the compound containing epoxy group is 300-800. Within the above range, the oligomer has better fluidity at room temperature, and is retained on the surface of the foam metal through wetting and capillary effect, and is evenly coated.

[0083] In one embodiment, the organic solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate (MPC), diphenyl carbonate (DPhC), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), γ-butyrolactone (γ-GBL), acetonitrile (AN), and cyclopentane sulfone (TMS).

[0084] In one embodiment, the current density of the electrochemical deposition is 0.1-0.5 mA / cm 2 , for example, it can be 0.1 mA / cm 2 , 0.2mA / cm 2 , 0.3mA / cm 2 , 0.4mA / cm 2 , 0.5mA / cm 2 Or a range consisting of any two values.

[0085] In one embodiment, the electrochemical deposition time is 0.5 to 6 hours, for example, it can be 0.5 hours, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours or a range consisting of any two values ​​therein.

[0086] In one embodiment, during the electrochemical deposition, the precursor is used as a working electrode, a platinum plate is used as a counter electrode, and a calomel electrode is used as a reference electrode.

[0087] A secondary battery in one embodiment of the present application includes a negative electrode, wherein the negative electrode includes the above-mentioned lithium metal three-dimensional porous material.

[0088] In one embodiment, the secondary battery further includes a positive electrode.

[0089] In one embodiment, the positive electrode comprises lithium foil.

[0090] In another embodiment, the positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material.

[0091] In one embodiment, the positive electrode active material can be selected from sodium iron composite oxide, sodium cobalt composite oxide, sodium manganese composite oxide, sodium nickel composite oxide, sodium nickel titanium composite oxide, sodium nickel manganese composite oxide, sodium iron manganese composite oxide, sodium nickel cobalt manganese composite oxide, sodium iron phosphate, sodium manganese phosphate, sodium cobalt phosphate, nickel cobalt manganese lithium and nickel cobalt aluminum lithium. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries can also be used. These positive electrode active materials can be used alone or in combination of two or more.

[0092] In one embodiment, the type of the positive electrode current collector is not particularly limited, and it can be any known material suitable for use as a positive electrode current collector. In one embodiment, the positive electrode current collector includes metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and carbon materials such as carbon cloth and carbon paper.

[0093] There is no particular restriction on the form of the positive electrode current collector. When the positive electrode current collector is a metal material, the positive electrode current collector may be in the form of metal foil, metal cylinder, metal strip roll, metal plate, metal foil, metal plate mesh, stamped metal, foamed metal, etc. When the positive electrode current collector is a carbon material, the positive electrode current collector may include but is not limited to a carbon plate, a carbon film, a carbon cylinder, etc.

[0094] In one embodiment, the positive electrode active material layer further includes a conductive agent and a binder.

[0095] In one embodiment, the type of the conductive agent mentioned in the present application is not limited, and any known conductive agent can be used.

[0096] In one embodiment, the conductive agent includes at least one of carbon materials such as acetylene black, needle coke, carbon nanotubes, and graphene.

[0097] In one embodiment, the type of binder mentioned in the present application is not limited, and any known positive electrode binder can be used.

[0098] In one embodiment, the binder includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, nitrocellulose, styrene-butadiene rubber, nitrile rubber, fluororubber, isoprene rubber, polybutadiene rubber, ethylene-propylene rubber, styrene-butadiene-styrene block copolymer or its hydrogenate, ethylene-propylene-diene terpolymer, styrene-ethylene-butadiene-ethylene copolymer, styrene-isoprene-styrene block copolymer, isotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymer, propylene-α-olefin copolymer, polyvinylidene fluoride, polytetrafluoroethylene, fluorinated polyvinylidene fluoride, and polytetrafluoroethylene-ethylene copolymer.

[0099] In the secondary battery mentioned in the present application, a separator is usually provided between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator are not particularly limited as long as the effect of the present application is not significantly impaired.

[0100] In one embodiment, the separator includes a porous sheet or non-woven fabric having excellent liquid retention. The materials of the resin or glass fiber separator include, but are not limited to, polyolefin, aromatic polyamide, polytetrafluoroethylene, polyethersulfone, and the like.

[0101] In one embodiment, the polyolefin is polyethylene or polypropylene. The above-mentioned materials of the diaphragm can be used alone or in any combination.

[0102] In one embodiment, the secondary battery may include an outer package, which can be used to encapsulate the electrode assembly and the electrolyte.

[0103] In one embodiment, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0104] In one embodiment, the secondary battery includes an electrolyte, and the type of the electrolyte of the secondary battery is not subject to specific restrictions. The electrolyte of the secondary battery includes an electrolyte salt and an organic solvent, and the specific types of the electrolyte salt and the organic solvent are not subject to specific restrictions and can be selected according to actual needs. The electrolyte may also include additives, and the types of the additives are not particularly limited. They can be film-forming additives for the positive electrode and / or the negative electrode, or additives that can improve certain properties of the battery, such as additives that improve the high or low temperature performance of the battery.

[0105] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape.

[0106] An embodiment of the present application provides an electric device, comprising the secondary battery described above, wherein the secondary battery serves as a power supply for the electric device.

[0107] Exemplarily, the above-mentioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0108] The following examples are provided to facilitate understanding of the present invention. These examples are not provided to limit the scope of the claims.

[0109] Example 1

[0110] A method for preparing a lithium metal three-dimensional porous material comprises the following steps:

[0111] Rolling a copper foam having a thickness of 200 μm (hereinafter referred to as initial thickness), a porosity of 80% (hereinafter referred to as initial porosity), and an average pore size of 50 μm under a pressure of 10 MPa until the thickness is 80 μm; heat-treating the rolled copper foam at 250° C. for 4 h in a mixed atmosphere of argon and hydrogen (volume ratio of 19:1) to obtain a pretreated copper foam;

[0112] LiFSI and PEGDE (polyethylene glycol diglycidyl ether) with Mn=500 were mixed evenly (LiFSI concentration was 0.06mmol / ml), and then the pretreated copper foam was immersed in the reaction solution, taken out and placed in an oven at 85°C for 300min for thermal induction in situ polymerization to form a PEO layer on the periphery of the copper foam to obtain a precursor;

[0113] EC:EMC was prepared into an organic solvent in a volume ratio of 3:7, and the organic solvent and 1M lithium hexafluorophosphate were prepared into an electrolyte. The precursor was used as a working electrode, a platinum plate was used as a counter electrode, and a calomel electrode was used as a reference electrode. The reaction was carried out at 0.4 mA / cm 2 The three-dimensional porous material of lithium metal was obtained by electrochemical deposition for 2.061h at a current density of .

[0114] The lithium metal three-dimensional porous material prepared in Example 1 includes a substrate layer and a PEO layer at least partially coated on the periphery of the substrate layer, and the substrate layer includes copper foam and lithium metal filled in the pores of the copper foam.

[0115] The parameters of Example 1 are shown in Table 1.

[0116] Embodiments 2 to 6

[0117] The difference between Examples 2 to 6 and Example 1 is that Examples 2 to 6 change the molecular weight of PEO by changing the heating temperature and time, thereby changing the ionic conductivity and the electronic conductivity.

[0118] Embodiments 7 to 10

[0119] The difference between Examples 7 to 10 and Example 1 is that Examples 7 to 10 change the initial porosity of the copper foam, thereby changing the porosity of the base layer.

[0120] Examples 11 to 16

[0121] The difference between Examples 11 to 16 and Example 1 is that Examples 11 to 16 change B by adjusting the current density and deposition time of the electrochemical deposition step.

[0122] Examples 17 to 20

[0123] The difference between Examples 17 to 20 and Example 1 is that Examples 17 to 20 change the average pore size of the foam copper.

[0124] Examples 21 to 24

[0125] The difference between Examples 21 to 24 and Example 1 is that Examples 21 to 24 change the lithium salt concentration and the molecular weight of PEGDE, thereby changing the thickness of the PEO layer.

[0126] Comparative Example 1

[0127] A method for preparing a lithium metal three-dimensional porous material comprises the following steps:

[0128] Rolling a copper foam having a thickness of 200 μm (hereinafter referred to as initial thickness), a porosity of 80% (hereinafter referred to as initial porosity), and an average pore size of 50 μm under a pressure of 10 MPa until the thickness is 80 μm; heat-treating the rolled copper foam at 250° C. for 4 h in a mixed atmosphere of argon and hydrogen (volume ratio of 19:1) to obtain a pretreated copper foam;

[0129] PEO (commercially available, with a viscosity-average molecular weight of 50W) was mixed evenly with water, and the pretreated copper foam was immersed in the reaction solution. After being taken out, it was placed in an oven at 85°C for 300 minutes to dry the water, and a PEO layer was formed on the periphery of the copper foam to obtain a precursor;

[0130] EC:EMC was prepared into an organic solvent in a volume ratio of 3:7, and the organic solvent and 1M lithium hexafluorophosphate were prepared into an electrolyte. The precursor was used as a working electrode, a platinum plate was used as a counter electrode, and a calomel electrode was used as a reference electrode. The reaction was carried out at 0.4 mA / cm 2 The three-dimensional porous material of lithium metal was obtained by electrochemical deposition for 2.061h at a current density of .

[0131] Comparative Example 2

[0132] A method for preparing a lithium metal three-dimensional porous material comprises the following steps:

[0133] Rolling a copper foam having a thickness of 200 μm (hereinafter referred to as initial thickness), a porosity of 80% (hereinafter referred to as initial porosity), and an average pore size of 50 μm under a pressure of 10 MPa until the thickness is 80 μm; heat-treating the rolled copper foam at 250° C. for 4 h in a mixed atmosphere of argon and hydrogen (volume ratio of 19:1) to obtain a pretreated copper foam;

[0134] LiFSI and N-doped polypyrrole with Mn=500 were mixed evenly (LiFSI concentration was 0.06mmol / ml), and then the pretreated copper foam was immersed in the reaction solution, taken out and placed in an oven at 85°C for 300min for thermal initiation in situ polymerization to form a PEO layer on the periphery of the copper foam to obtain a precursor;

[0135] EC:EMC was prepared into an organic solvent in a volume ratio of 3:7, and the organic solvent and 1M lithium hexafluorophosphate were prepared into an electrolyte. The precursor was used as a working electrode, a platinum plate was used as a counter electrode, and a calomel electrode was used as a reference electrode. The reaction was carried out at 0.4 mA / cm 2 The three-dimensional porous material of lithium metal was obtained by electrochemical deposition for 2.061h at a current density of .

[0136] Comparative Example 3

[0137] The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 is not immersed in the reaction liquid and thus does not include a PEO layer.

[0138] Comparative Example 4

[0139] The difference between Comparative Example 4 and Example 1 is that no electrochemical deposition is performed in Comparative Example 4, and thus lithium metal is not filled inside the copper foam.

[0140] Table 1

[0141]

[0142] Performance Testing

[0143] Test method for the cycle capacity retention rate of secondary batteries: Cut the sheets obtained in the comparative example and the embodiment into 19mm small discs as the negative electrode, mix the ternary material NCM811, polyvinylidene fluoride PVDF and carbon black in a ratio of 8:1:1, add nitrogen methyl pyrrolidone NMP to disperse, and then use a scraper to evenly coat it on the aluminum foil current collector, and dry it at 100°C to obtain the positive electrode. Cut the positive electrode into 16mm small discs as the positive electrode, assemble 2430 buckle batteries, where the electrolyte formula of the secondary battery is 1M LiPF6 EC / EMC electrolyte, EC:EMC=3:7, and the diaphragm uses a 14μm thick PE diaphragm. The buckle battery is cycled at a rate of 0.5C charge and 1C discharge, and the capacity retention rate is stopped below 80%, and the number of cycles at this time is recorded.

[0144] Thickness change rate: The sheets obtained in the comparative example and the example were cut into 19 mm small discs and assembled with 16 mm commercial lithium foil into a 2430 button half-cell, wherein the electrolyte formula was 1M LiPF6 EC / EMC electrolyte, EC:EMC=3:7, and the separator was a 14 μm thick PE separator. After a capacity of 1 mAh / cm2 was deposited on the negative electrode side with a current of 1 mA / cm2, the button was disassembled, the negative electrode was taken out, and the thickness of the electrode was measured to obtain the thickness change rate before and after deposition.

[0145] Table 2

[0146]

[0147]

[0148] As can be seen from Table 2, the base layer of the lithium metal three-dimensional porous material described in the present application is a three-dimensional conductive metal filled with metallic lithium, the PEO (polyethylene oxide) layer is at least partially coated on the periphery of the base layer, and the ionic conductivity of the polymer layer is 10 -5 ~1S / cm, electronic conductivity is 10 -9 ~10 -5S / cm, and presents a three-dimensional porous structure as a whole. The lithium metal three-dimensional porous material has the characteristics of high specific surface area and high interface stability, which can effectively increase the interface stability. The polymer layer can isolate the direct contact between the lithium metal and the electrolyte, and reduce the side reaction of the contact between the two. The matrix layer provides highly active deposition sites and sufficient deposition space for lithium ions during the charging process, and slowly releases the compressive stress during the charging and discharging process and the rolling process, thereby effectively improving the cycle performance of the secondary battery.

[0149] By comparing Examples 1 to 7 to 10, it can be seen that the porosity of the matrix layer is optimally in the range of 10%-30%. If the porosity is too low, there will not be enough space to accommodate lithium metal during battery charging and discharging, resulting in large volume expansion. At the same time, the lithium metal that exceeds the collective layer will be deposited on the surface, which is prone to generate dendrites and shorten the cycle life. When the porosity is too large, the lithium ion transmission path becomes longer, and lithium ions tend to deposit on the surface and near the surface. The utilization rate of the matrix layer is insufficient, and the lithium metal cannot be densely deposited, which also leads to dendrite growth.

[0150] By comparing Examples 1 and 11 to 16, it can be seen that the proportion of lithium metal plays an important role in improving the cycle life. This is because lithium metal consumption is inevitable during the cycle, and the stock of lithium metal will offset the consumption of side reactions or dead lithium generation.

[0151] By comparing Examples 1 and 17 to 20, it can be seen that the average pore size of the copper foam also affects the cycle life. This is because the pore size can adjust the deposition behavior of lithium ions. A pore size that is too small or too large is not conducive to the rapid transmission of lithium ions.

[0152] By comparing Examples 1 and 21 to 24, it can be seen that the thickness of the PEO layer has an impact on the cycle life. This is because the thickness of PEO can affect its mechanical modulus. During the charge and discharge process, the role of the PEO layer is not only to isolate the direct contact between lithium metal and the electrolyte, but also to induce plastic deformation of local lithium dendrites. Therefore, the PEO layer needs to have a certain thickness to effectively reduce the risk of dendrite puncture. When the PEO layer is too thick, the transmission of lithium ions becomes more difficult, the path becomes longer, and it is not conducive to the uniform deposition of lithium metal, which leads to a decrease in life.

[0153] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A lithium metal three-dimensional porous material, characterized in that: The invention comprises a substrate layer and a polymer layer at least partially covering the periphery of the substrate layer, wherein the substrate layer comprises a three-dimensional conductive metal and lithium metal filled in pores of the three-dimensional conductive metal; The ionic conductivity of the polymer layer is 10 -5 ~1S / cm, electronic conductivity is 10 -9 ~10 -5 S / cm.

2. The lithium metal three-dimensional porous material according to claim 1, characterized in that: The ionic conductivity of the polymer layer is 5.4*10 -5 ~8.9*10 -4 S / cm, the electronic conductivity is 7.4*10 -7 ~2.1*10 -5 S / cm.

3. The lithium metal three-dimensional porous material according to claim 1, characterized in that: The porosity of the base layer is A, 10%≤A≤30%.

4. The lithium metal three-dimensional porous material according to claim 1, characterized in that: The three-dimensional conductive metal comprises at least one of foamed copper, foamed nickel and foamed aluminum; and / or The average pore size of the three-dimensional conductive metal is 20 to 80 μm.

5. The lithium metal three-dimensional porous material according to claim 1, characterized in that: The mass percentage of the lithium metal in the matrix layer is B, which satisfies: 0.2%≤B≤1%.

6. The lithium metal three-dimensional porous material according to any one of claims 4 to 5, characterized in that: Satisfies: 10≤A / B≤125.

7. The lithium metal three-dimensional porous material according to claim 1, characterized in that: The thickness of the three-dimensional conductive layer is 2 to 350 μm; and / or The thickness of the polymer layer is 0.5-20 μm.

8. The lithium metal three-dimensional porous material according to claim 1, characterized in that: The viscosity average molecular weight of the polymer in the polymer layer is 100,000 to 10,000,000.

9. A method for preparing a lithium metal three-dimensional porous material, characterized in that: The following steps are involved: Rolling and heat treating the three-dimensional conductive metal to obtain a pretreated three-dimensional conductive metal; placing the pretreated three-dimensional conductive metal in a reaction solution, reacting to obtain a precursor; Placing the precursor in an electrolyte for electrochemical deposition to obtain a lithium metal three-dimensional porous material; The reaction solution includes a first lithium salt and a compound containing at least one of a halogen group, a sulfonate group, a sulfate group, and an epoxy group; The electrolyte includes a second lithium salt and an organic solvent.

10. The method for preparing a lithium metal three-dimensional porous material according to claim 9, characterized in that: Satisfy at least one of (a) to (h): (a) the temperature of the heat treatment is 200 to 300° C., and the time of the heat treatment is 0.5 to 6 hours; (b) the heat treatment is carried out in a mixed atmosphere of argon and hydrogen, wherein the volume ratio of hydrogen to argon is (0.5-2):(18-19.5); (c) the reaction temperature is 50 to 100° C., and the reaction time is 10 to 600 min; (d) the concentration of the first lithium salt in the reaction solution is 0.05 to 0.8 mmol / L; (e) the concentration of the second lithium salt in the electrolyte is 0.5 to 2 mol / L; (f) the first lithium salt and the second lithium salt each independently include at least one of LiTFSI, LiFSI, LiPF6, and LiBF4; (g) The molecular formula of the compound containing epoxy group is C3H5O2-(C2H4O) n -C3H5O; (h) The number average molecular weight of the compound containing at least one of a halogen group, a sulfonate group, a sulfate group, and an epoxy group is 300 to 800.

11. A secondary battery, characterized in that: It comprises a negative electrode, wherein the negative electrode comprises the lithium metal three-dimensional porous material according to any one of claims 1 to 8.

12. An electrical device, characterized in that: The secondary battery according to claim 11 is included.

Citation Information

Patent Citations

  • Spume lithium cathode of lithium metal secondary batteries and method for producing the same

    CN101162772A

  • Three-dimensional composite metal lithium negative electrode, preparation method thereof, lithium metal battery and lithium-sulfur battery

    CN110112367A

  • Three-dimensional porous metal lithium negative electrode for secondary battery and preparation and application thereof

    CN111799443A

  • Composite lithium metal negative electrode, preparation method thereof and lithium secondary battery

    CN111864180A

  • Composite pole sheet and manufacturing method thereof, and lithium ion battery

    CN112038585A